Charge carrier transfer in tungsten disulfide—black phosphorus heterostructures. (31st October 2017) - Zhao, Siqi; He, Dawei; Wang, Yongsheng; Zhang, Xinwu; He, Jiaqi
Abstract: Photocarrier dynamics in tungsten disulfide—black phosphorus (BP) heterostructures were studied by time-resolved differential reflection measurements. The heterostructures were fabricated by stacking together monolayer WS2 and BP flakes that are both fabricated by mechanical exfoliation. Efficient and ultrafast transfer of photocarriers from WS2 to BP flakes was observed. This confirms the type-I band alignment of WS2 /BP heterostructures that was predicted by theory. Accompanied with the photocarrier interlayer transfer process from WS2 to BP flakes, the change of the absorption of WS2 persists for several nanoseconds. These results promote the consciousness about the carrier dynamics of interlayer transfer process in van der Waals heterostructures and its application in optoelectronic devices.